2014
DOI: 10.3892/etm.2014.2063
|View full text |Cite
|
Sign up to set email alerts
|

Significance of human epidermal growth factor receptor 2 expression in colorectal cancer

Abstract: The aim of the present study was to evaluate the protein expression level of human epidermal growth factor receptor 2 (HER-2) using immunohistochemistry (IHC), and assess the association with clinicopathological parameters and the prognosis of patients with colorectal cancer (CRC). In addition, the current study observed the consistency between the levels of HER-2 protein expression determined by IHC and HER-2 gene amplification determined by fluorescence in situ hybridization (FISH) in the CRC samples. Overex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…[6][7][8][9][12][13][14][15][16][17][18][19][20] The present study is unique because the only study with an equally large sample size, albeit without clinical validation, reported much lower rates of both ERBB2 expression (2.7%) and positive amplification (1.6%). 8 This difference very likely resides in the fact that while our findings have been obtained on a primarily metastatic population, Heppner et al 8 tested only primary tumors using a different staining antibody (SP3) and a different in situ hybridization method (CISH), and employed gastric cancer criteria to test and score the samples.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…[6][7][8][9][12][13][14][15][16][17][18][19][20] The present study is unique because the only study with an equally large sample size, albeit without clinical validation, reported much lower rates of both ERBB2 expression (2.7%) and positive amplification (1.6%). 8 This difference very likely resides in the fact that while our findings have been obtained on a primarily metastatic population, Heppner et al 8 tested only primary tumors using a different staining antibody (SP3) and a different in situ hybridization method (CISH), and employed gastric cancer criteria to test and score the samples.…”
Section: Discussionmentioning
confidence: 74%
“…Recently, we and others have found that activation of ERBB2 signaling causes resistance to anti-EGFR therapy in a fraction of metastatic colorectal patients, wild type for RAS codons 12-13. [10][11][12] Of more relevance for the clinic, we have demonstrated that the combination of the anti-ERBB2 monoclonal antibody trastuzumab and the dual EGFR/HER2 small-molecule inhibitor lapatinib, but not either drug alone, is effective in inducing durable tumor shrinkage in ERBB2-amplified metastatic CRC patient-derived xenografts. 10 Reasoning that ERBB2 corsivo could also represent a valuable therapeutic target in KRAS wild-type metastatic colorectal cancer patients resistant to anti-EGFR treatment, we designed the HERACLES trial, a phase II trial testing the combination of trastuzumab and lapatinib in ERBB2-positive metastatic colorectal cancer patients refractory to standard treatment, including cetuximab or panitumumab.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of Ki-67 in nude mice injected with A549 cells was measured using immunohistochemistry. The immunohistochemistry assay was conducted according to previous report (18). The sections were treated with rabbit polyclonal anti-Ki-67 antibody (1:100; cat.…”
Section: Reverse Transcription-quantitative (Rt-q)pcr Totalmentioning
confidence: 99%
“…Survival rates have increased with the introduction of irinotecan and oxaliplatin chemotherapy, as well as the use of targeted therapies in the past decade (68). Combined perioperative chemotherapy and surgery is a major therapeutic treatment for patients with initially resectable liver metastases from CRC (911). However, the development of drug resistance in cancer cells raises a major challenge to chemotherapy and restricts the anticancer efficacy of chemotherapeutic drugs (1214).…”
Section: Introductionmentioning
confidence: 99%